The Chikungunya virus: A reemerging cause of acute febrile illness in the high jungle of northern Peru - Aguilar-Luis, Miguel Angel (2023)
Background The Chikungunya virus (CHIKV) is an emerging arthropod-borne virus (arbovirus) that causes undifferentiated acute febrile illness. Cases of CHIKV may be under-reported in Peru, given the various difficulties in diagnosing it, such as lack of diagnostic tests in remote areas, the passive nature of epidemiological surveillance, and co-circulation of other arthro-pod-borne pathogens. Therefore, a study was conducted in the high jungle of northern Peru to determine the prevalence of CHIKV among febrile patients and describe their clinical characteristics. Methods A cross-sectional study was conducted in the province of Jaen, Cajamarca, located in the high jungle of northern Peru. Patients attending primary healthcare centers within Cajamar-ca’s Regional Health Directorate were enrolled. The study took place from June 2020 through June 2021. Patients were eligible if they sought outpatient healthcare for a clinical diagnosis of acute febrile illness (AFI). Serum samples were collected from all patients, and the diagnosis of CHIKV was determined using real-time RT-PCR, as well as the detection of IgM antibodies by ELISA. A logistic regression model was employed to identify the risk factors for CHIKV, and the odds ratios (ORs) were calculated, along with their corresponding 95% confidence intervals (95% CI). Results A total of 1 047 patients with AFI were included during the study period. CHIKV was identified in 130 patients of 1 047 (12.4%). Among the CHIKV positive cases, 84 of 130 (64.6%) were diagnosed by RT-PCR, 42 of 130 (32.3%) by IgM ELISA detection, and 4 of 130 (3.1%) by both assays. The majority of patients with CHIKV infection fell within the 18–39 years age group (50.0%), followed by the 40–59 years age group (23.9%) and those with 60 years or older (10.8%). The most common clinical symptoms observed in patients with CHIKV infection were headache (85.4%), myalgias (72.3%), and arthralgias (64.6%). The highest number of positive CHIKV cases occurred in May (23.1%), followed by March (20.0%) and February (13.8%) of 2021. Conclusion The study reports a considerable frequency of CHIKV infections among patients with AFI from the high jungle of northern Peru. These findings highlight the importance of recognizing CHIKV as an ongoing pathogen with continuous transmission in various areas of Peru. It is crucial to enhance epidemiological surveillance by implementing reliable diagnostic tech-niques, as the clinical symptoms of CHIKV infection can be nonspecific.